Factors affecting NBA game performance over the course of a season - Russell, J. L.; McLean, B. D.; Stolp, S.; Strack, D.; Coutts, A. J. (Journal of Sports Sciences, 2025)
The NBA season presents unique challenges, including dense schedules, frequent travel and sleep disruption. To manage these demands, practitioners track training load, travel variables and athlete-reported outcome measures (AROMs), which reflect subjective perceptions of fatigue, sleep and soreness. Despite their widespread use in professional sports, no prior studies have assessed how these factors jointly influence player well-being and performance across an NBA season. This study examined the impact of on-court training load and travel demands on AROM responses and individual in-game performance among 14 NBA players. Data included training load, travel-related variables (elevation, time zone changes, nights away), AROMs and game performance metrics. Multi-level modelling (MLM) assessed relationships between 5- and 10-day cumulative loads, travel demands and performance outcomes. Results showed that defensive performance varied significantly with elevation (p = 0.005), time zone acclimation (p = 0.055) and 5-day load (p = 0.065). Time zone acclimation also negatively influenced mood, though other AROMs (fatigue, soreness, sleep and stress) were unaffected. This is the first study to simultaneously evaluate training load, travel and subjective wellness in relation to NBA game performance, offering new insight into the complex demands of the professional basketball season.